NIGERIA’S INTRACTABLE CRISIS OF NATIONAL INSECURITY AND THE RESPONSE OF THE SOUTHWESTERN STATES - Sunday Owen, ABANG PhD; ADEYEMI-SUENU, Adebowale(PhD) (International Studies Journal)
This study has as its primary objective among others, the examination of the nature, reasons and challenges of insecurity in the South-west region of Nigeria, as well as the seemingly unchecked and continuous penetration of the region’s forests by kidnappers and other criminal elements. Currently, all the six geo-political zones in Nigeria have witnessed serious security threats ranging from kidnapping to armed robbery, ritual killings, banditry, cultism, cattle rustling, herdsmen-farmers clashes, and wanton destruction of properties. This is in the face of the Nigeria Police Force found incapable to rise up to this national security challenge. To make up for this apparent insecurity, the South-west region instituted a regional security alternative Amoteku. This paper looks at the cause for introducing the Amotekusecurity outfit in the South-west and its implication on Nigeria national security.The paper relied on secondary data sourced from journals, newspapers, relevant books, materials from the internet and government publications, and interview of some individuals to ascertain the usefulness of the Amotekusecuritynetwork. The study reveals that the establishment of Amotekuby the South-west Governors to complement theNigeriaPolice Force has proved ineffective, and there is need for community policing and enhancement of the police force to confront this national threat.